Gonadotropin-releasing hormone improves conception rates of repeat-breeders with previous reproductive disorders - Jeffrey S. Stevenson; Edward P. Call (Kansas Agricultural Experiment Station Research Reports, 1987)
An experiment examining the benefit of treating repeat-breeders with 100 µg GnRH (Cystorelin ®) at the time of third or fourth insemination was conducted in 513 dairy cows of which 93 (abnormal cows) had been diagnosed previously (during the 60 to 90 days postpartum) as having reproductive disorders, including retained placenta, uterine infections, prolonged anestrus, and cystic ovaries. Treatment with GnRH improved conception in normal and abnormal repeat-breeding cows by 13 percentage points or 42%.; Dairy Day, 1987, Kansas State University, Manhattan, KS, 1987;
Keywords: Kansas Agricultural Experiment Station contribution; no. 88-114-S; Report of progress (Kansas Agricultural Experiment Station); 527; Dairy; Gonadotropin-releasing hormone (GnRH); Conception rate; Reproductive disorders